Density Control-Based Algorithms for Dynamic Maintenance in Sensor Networks with Limited Mobility - Wei-Jhih Lin; Kuen-Ding Lin; Lai, K Robert (2010 IEEE 24th International Conference on Advanced Information Networking and Applications Workshops, 2010)
This paper proposes a fully distributed, density-control, and multi-hop dynamic maintenance algorithm (DCMA) to repair the coverage holes in wireless sensor networks. Decision and movement of the nodes are autonomous and involve only limited distance to maintain the connectivity. While maintaining the coverage and connectivity, the proposed algorithm aims at minimizing average moving distance and energy consumption of sensor nodes. Further, it takes the density measures into consideration when deciding which node to move and to what direction and distance to improve the non-uniform distribution of sensor nodes. Simulation results reveal that the proposed algorithm performs better than other maintenance algorithms in terms of coverage, convergence, energy consumption, uniformity, and sensitivity of communication range.